Factors affecting health promotion behavior of school-aged children in South Korea: a cross-sectional study. - Lim, Bo Ra; Kim, Dong Hee; Cho, Chung Min (Child Health Nursing Research, 2025)
Purpose: This study aimed to identify the factors affecting the health promotion behavior of school-aged children informed by the Information-Motivation-Behavioral Skills Model. Methods: A cross-sectional study was conducted with 209 fifth- and sixth-grade elementary school students from Seoul, selected through convenience sampling. Data were collected from March 13 to 31, 2023, using a self-administered questionnaire. The questionnaire included validated tools that measured health literacy, attitude toward health behaviors, social support, self-efficacy, and health promotion behavior. Data were analyzed using descriptive statistics, Pearson's correlation, and stepwise multiple regression, using IBM SPSS/WIN ver. 29.0. Results: The factors influencing the health promotion behavior of school-aged children were social support (β=.43, p<.001), attitude toward health behaviors (β=.27, p<.001), interest in health (high interest group) (β=.14, p=.003), self-efficacy (β=.13, p=.014), and health literacy (β=.10, p=.026). The explanatory power of the model was 63% (F=68.37, p<.001). Conclusion: Based on the results of this study, it is highly recommended to develop and apply health education and health promotion programs that consider health literacy, attitude toward health behaviors, social support, self-efficacy, and interest in health to foster school-aged children's health promotion behavior.